Assistance of Halal Certification on UKMM Product, Cibeusi Village, Ciater Distrik, Subang Regency: Pendampingan Sertifikat Halal pada Produk UKMM Desa Cibeusi Kecamatan Ciater Kabupaten Subang - Ujang Charda S; Ika Fauziyah; Restu Mahardhika (Yayasan Ahmar Cendekia Indonesia, 2022)
Halal certification is an activity or process carried out to meet certain standardization achievements with the aim of having formal legal recognition that the products that have been produced meet halal requirements. Cibeusi Village, Ciater District in Subang Regency has the potential for SMEs with a variety of processing in the food sector. Based on observations made during the KKNM activities, the village has 20 SMEs with 10% of SMEs having halal certificates. The service is carried out using the advocacy method. With the Self Declaration Program accompanied by the Halal Center of Muslim Scholars, it is carried out to make it easier for business actors to obtain halal labels on their product packaging. Thus, the activity received a positive response from various parties. Abstrak Sertifikasi halal adalah kegiatan ataupun proses yang dilakuan guna memenuhi capaian standarisasi tertentu dengan bertujuan untuk memiliki pengakuan legal formal bahwa produk yang telah diproduksi memenuhi ketentuan halal. Desa Cibeusi, Kecamatan Ciater di Kabupaten Subang memiliki potensi UKM dengan ragam pengolahan dibidang pangan. Berdasarkan hasil pengamatan yang telah dilakukan selama kegiatan KKNM, desa tersebut memiliki UKM berjumlah 20 dengan 10% UKM yang telah memiliki sertifikat halal. Pengabdian dilakukan dengan metode advokasi. Dengan Program Self Declare didampingi Halal Center Cendekia Muslim dilakukan untuk mempermudah para pelaku usaha dalam memperoleh label halal pada kemasan produknya. Dengan demikian kegiatan tersebut mendapat respon positif dari berbagai pihak.